Monitoring Antibiotic Usage in German Dairy and Beef Cattle Farms—A Longitudinal Analysis - Hommerich, Katharina; Ruddat, Inga; Hartmann, Maria; Werner, Nicole; Käsbohrer, Annemarie; Kreienbrock, Lothar (Frontiers in Veterinary Science, 2019)
It is evident, that the development of antimicrobial resistance is related to the magnitude of antibiotic use. To analyze associations between rising antimicrobial resistances and usage of antimicrobial agents, data from monitoring and surveillance systems are crucial. Within the project VetCAb (Veterinary Consumption of Antibiotics), antibiotic usage data in German livestock regularly is collected and evaluated. Based on a cross-sectional study in 2011, the project is continued as a longitudinal study VetCAb-Sentinel with ongoing participant recruitment and data collection since 2013. The data collection is based on official German application and delivery forms (ADF), voluntarily provided by veterinarians and farmers. In this study the results of antibiotic consumption data of dairy cows, dairy calves and beef cattle are described, using a semi-annual treatment frequency, analyzing 95,944 ADF issued between 2011 and 2015. Results show that the median of the treatment frequency in dairy calves (0.4-0.3) and beef cattle (0.2-0) holdings slightly decreased, whereas the median in dairy cow holdings ranged between 1.9 and 2.3 during the observed period. Temporal changes and the effect of the factors "farm size" and "region" on the treatment frequency were investigated, using multiple linear mixed and logistic regression models. Generally, the factor "time" has a statistically significant impact on the treatment frequency in all production types. In addition a temporal trend test over the first six half-years shows that an increasing linear trend can be stated in dairy cows and dairy calves (p=0.017; p =0.004 respectively). If the time-period is extended to all eight half-years under study, this turns into a quadratic effect (dairy cows: p=0.006; dairy calves: p <0.001). In dairy calves and beef cattle, also the factor "farm size" has a statistically significant impact. The factor "region", in contrast, shows no statistically significant impact at all. Compared to other livestock populations in Germany, the use of antimicrobials in dairy cows, dairy calves and beef cattle appears to be low, but varies across several associated factors. Considering these effects, it is recommended that the size of dairy calf and beef cattle holdings is regularly considered in the evaluation of antimicrobial use data over time.